Harvesting Hope A Socioeconomic Analysis of Rural Life during Sikh Rule - AZHAR RASHID KHANDAY; DR. JASVANT KUMAR YADAV (Innovative Research Thoughts, 2023)
Backdrop, but also gives a detailed picture of how the lives of rural inhabitants were influenced by Sikh monarchs. The research presents a nuanced view on the evolution of rural landscapes throughout this time period by examining topics such as agriculture, commerce, government, and social structures. This allows for the creation of a more complete picture. It shows the multidimensional character of Sikh governance, highlighting both the beneficial contributions that it made and the hardships that were encountered by the rural inhabitants during that time. This study is an important contribution to the academic literature on Sikh history and rural studies. It provides a comprehensive analysis that deepens our understanding of a pivotal period in world history and enlarges our knowledge of the subject as a whole.